2020
DOI: 10.1212/nxi.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Increased HLA-DR expression and cortical demyelination in MS links with HLA-DR15

Abstract: ObjectiveTo investigate molecular changes in multiple sclerosis (MS) normal-appearing cortical gray matter (NAGM).MethodsWe performed a whole-genome gene expression microarray analysis of human brain autopsy tissues from 64 MS NAGM samples and 42 control gray matter samples. We further examined our cases by HLA genotyping and performed immunohistochemical and immunofluorescent analysis of all human brain tissues.ResultsHLA-DRB1 is the transcript with highest expression in MS NAGM with a bimodal distribution am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…However, while NAWM microglia have a lipid signature, NAGM microglia have increased expression of genes related to glycolysis and iron homeostasis ( SCL25A37, ABCB6 ) and a neurodegenerative profile ( CXCR4, GPNMB, OPN/SPP1 ) ( Figure 3 ). Furthermore, in HLADRB1*15:01 positive patients, HLA-DRB1 and B5 were the highest expressed genes in NAGM ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, while NAWM microglia have a lipid signature, NAGM microglia have increased expression of genes related to glycolysis and iron homeostasis ( SCL25A37, ABCB6 ) and a neurodegenerative profile ( CXCR4, GPNMB, OPN/SPP1 ) ( Figure 3 ). Furthermore, in HLADRB1*15:01 positive patients, HLA-DRB1 and B5 were the highest expressed genes in NAGM ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the cooperation of DR2a and DR2b may increase the fitness to cope with viral infection but also the risk of pathogenic autoreactivity. A recent study documented that DR2a and DR2b are expressed highly in normal-appearing gray matter in MS brains ( Enz et al., 2019 ), the region where RASGRP2 is found in cortical neurons ( Jelcic et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…DRB1*15:01 and DRB5*01:01 are the two genes with highest differential expression in normal appearing gray matter of the brains of MS patients [66].…”
Section: Trends In Geneticsmentioning
confidence: 97%
“…Furthermore, studies of DR2a and DR2b expression by different immune cells, but also in the thymus and the brain of MS patients, demonstrated that both alleles are always coexpressed, although at varied levels in different cell types [65]. A recent study of gene expression in normal-appearing cortical gray matter in MS patients surprisingly demonstrated that the most strongly upregulated genes are DR2b and DR2a, even in the absence of overt signs of inflammation or damage [66]. Most likely, microglial cells are responsible for these changes.…”
Section: Trends In Geneticsmentioning
confidence: 99%